A teoria da personalidade em Bergson - Morais, Yago Antonio de Oliveira (Universidade Federal de São Carlos, 2024)
The aim is to investigate and analyze the question of personality in Bergson. Our aim is to explore some necessary conditions for thinking about personality, both the properties of the notion of consciousness as duration and some considerations about the role played by the body. We will look in particular at Bergson's three main works, Essai sur les données immédiates de la conscience, Matière et mémoire and L'évolution créatrice. We will follow how the philosopher rethought interiority, considering it in relation to the living body, as well as exploring the notion of life, the main aspects of which are related to these elements. Bergson defends a concept of personality linked to consciousness, which is therefore psychological, but which is also linked to its physical basis, the body. The notion of personality, in this sense, is circumscribed as something between these two domains, both thought of in the light of duration. Our proposal, then, consists of arguing that there is a theory established by the philosopher that converges with his philosophy of duration.
La théorie de la personnalité chez Bergson
Bergson's theory of personality
Keywords: Personalidade; Consciência; Duração; Corpo; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA